1989
DOI: 10.1073/pnas.86.23.9621
|View full text |Cite
|
Sign up to set email alerts
|

Role of the hypothalamus in the control of atrial natriuretic peptide release.

Abstract: Stimulation of the region antero-ventral to the third cerebral ventricle (AV3V) by a cholinergic drug, carbachol, and lesions of the AV3V have been demonstrated in previous studies to either augment or decrease sodium excretion, respectively. Atrial natriuretic peptide (ANP) dramatically increases renal sodium excretion and has been localized to brain areas previously shown to be involved in control of sodium excretion. Consequently, to evaluate a possible role of brain ANP in evoking the changes in renal sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 30 publications
2
37
2
Order By: Relevance
“…In view of the much larger quantities of the peptide stored in the atria, it is probable that changes in atrial release contribute to the alterations in plasma ANP observed after stimulation or ablation of the AV3V region; however, these results suggested that the dramatic changes in plasma ANP that followed these manipulations may be due to altered release of the peptide from brain structures as well as the atria and lungs (38,39). These stimulation and lesion experiments support a crucial role of the CNS in controlling ANP release.…”
Section: Brain Anpergic Neuronal System and Release Of Anpcontrasting
confidence: 50%
See 1 more Smart Citation
“…In view of the much larger quantities of the peptide stored in the atria, it is probable that changes in atrial release contribute to the alterations in plasma ANP observed after stimulation or ablation of the AV3V region; however, these results suggested that the dramatic changes in plasma ANP that followed these manipulations may be due to altered release of the peptide from brain structures as well as the atria and lungs (38,39). These stimulation and lesion experiments support a crucial role of the CNS in controlling ANP release.…”
Section: Brain Anpergic Neuronal System and Release Of Anpcontrasting
confidence: 50%
“…Therefore, we evaluated the possible role of brain ANP in evoking the changes in renal sodium excretion that followed stimulations or lesions of the AV3V, a region further implicated in control of sodium excretion by later experiments (37). Injection of carbachol into the AV3V produced the expected natriuresis on the basis of our earlier experiments, which was accompanied by a dramatic rise in plasma ANP concentration and a rise in ANP content in the medial basal hypothalamus, the neurohypophysis and particularly the anterior hypophysis but without alterations in the content of ANP in the lungs or the right or left atrium (38). The marked elevations in content of the peptide in the basal hypothalamus and neuro-and adenohypophysis suggested that the natriuresis resulting from this stimulation is brought about at least in part by release of ANP from the brain.…”
Section: Brain Anpergic Neuronal System and Release Of Anpmentioning
confidence: 99%
“…20 Electrical stimulation of the rostral nucleus tractus solitarius raises the pANF concentration, 21 and stimulation of the region anteroventral to the third ventricle (AV3V) with carbachol produces a dramatic rise in circulating ANF levels. 22 In humans, the pANF concentration is elevated following SAH 9 -11 and intracerebral hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…ANP neurons (with cell bodies in the paraventricular nucleus projecting axons to the external layer of the median eminence (ME) and to the neural lobe) are important in AV3V mediated natriuresis (10). Cholinergic and adrenergic stimulation of AV3V increases sodium excretion, which is associated with a rapid increase in plasma ANP.…”
Section: Neural Control Of Hydromineral Homeostasismentioning
confidence: 99%